Towards a Disruptive Digital Platform Model - Erol Kazan (Copenhagen Business School (CBS), 2018)
Digital platforms are layered modular information technology architectures that support disruption. Digital platforms are particularly disruptive, as they facilitate the quick release of digital innovations that may replace established innovations. Yet, despite their support for disruption, we have not fully understood how such digital platforms can be strategically designed and configured to facilitate disruption. To that end, this thesis endeavors to unravel disruptive digital platforms from the supply perspective that are grounded on strategic digital platform design elements. I suggest that digital platforms leverage on three strategic design elements (i.e., business, architecture, and technology design) to create supportive conditions for facilitating disruption. To shed light on disruptive digital platforms, I opted for payment platforms as my empirical context and unit of analysis. Through primary and secondary data sources, findings suggest that digital platforms with an Analyzer and Prospector strategy profile have favorable conditions to facilitate disruption. It is envisioned that insights gleaned from multiple cases will contribute towards bridging existing knowledge gaps in strategic management, digital platforms, and open innovation literature.
hdl:10398/9640
Keywords: 650